2008
DOI: 10.1038/pcan.2008.21
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of psychological distress in men being investigated for the presence of prostate cancer

Abstract: High levels (450%) of anxiety are reported in patients undergoing screening for prostate cancer, which may affect health-related quality of life. We aimed to determine the level and prevalence of anxiety and depression and to identify those aspects of the diagnostic pathway that induce the most stress in men being investigated for prostate cancer. A total of 159 prostate-specific antigenunscreened men undergoing a transrectal ultrasound-guided biopsy of the prostate (TRUS-B) completed two questionnaires, prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 26 publications
4
53
0
Order By: Relevance
“…In an earlier longitudinal study of men being screened for prostate cancer, Gustafsson et al (1995) reported that cortisol level (indicating the degree of emotional stress) was highest immediately before being informed of the biopsy result, although levels decreased somewhat 2 weeks later in those who received a benign biopsy result. Other studies have concluded that testing for prostate cancer had little or no effect on men's psychological health (Brindle et al, 2006;Awsare et al, 2008). These studies relied on the Hospital Anxiety and Depression Scale (HADS) (Zigmond and Snaith, 1983), which was designed to detect clinical cases of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier longitudinal study of men being screened for prostate cancer, Gustafsson et al (1995) reported that cortisol level (indicating the degree of emotional stress) was highest immediately before being informed of the biopsy result, although levels decreased somewhat 2 weeks later in those who received a benign biopsy result. Other studies have concluded that testing for prostate cancer had little or no effect on men's psychological health (Brindle et al, 2006;Awsare et al, 2008). These studies relied on the Hospital Anxiety and Depression Scale (HADS) (Zigmond and Snaith, 1983), which was designed to detect clinical cases of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…These results, particularly that high levels of distress may be encountered by some men, should be included in information presented to men by GPs before they consent to receiving a test. For men undergoing testing, whether as part of screening, or in primary or secondary care, the concomitant collection of POMS and IES data could be used to identify men who are experiencing tension-anxiety and early distress symptoms at the time of the PSA test, and thus identify those who might benefit from additional support and information to prevent this developing into distress later on (see also Essink-Bot et al, 1998;Awsare et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Worry was assessed using two 100-mm visual analogue scales (VAS) [4]. The extremities were anchored at 'not worried at all' and 'extremely worried' in relation to the appointment and results of the appointment.…”
Section: Methodsmentioning
confidence: 99%
“…Emerging research has also found increased anxiety during earlier stages of the prostate cancer pathway when patients are undergoing prostatic investigation in response to positive screening tests [3] or referrals due to elevated prostate-specific antigen tests or abnormal digital rectal exams [4]. This suggests that some patients in the pre-diagnostic stage may experience anxiety as a result of the processes involved in this part of the diagnostic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, unknown whether the risk of injuries is also increased during the time period before the diagnosis. Evidence suggests that the diagnostic process of cancer entails severe emotional distress, regardless of the eventual result, [13][14][15][16][17] and could therefore increase the risk of non-iatrogenic injuries (intentional or unintentional). To this end, we analysed the risks of both iatrogenic and non-iatrogenic injuries during the weeks before and after diagnosis using a nationwide study sample in Sweden.…”
Section: Introductionmentioning
confidence: 99%